Owady w polskim i rosyjskim językowym obrazie świata - Kuligowska, Katarzyna (Studia Rossica Posnaniensia, 2018)
The paper is devoted to insects in Polish and Russian linguistic views of the world. The figurative meanings, derivational potential and semantic connotations of insects’ names, as well as idioms have been analysed to reveal the position of these animals in the language awareness of Poles and Russians.